Maxillary control with functional appliances: some clinical observations - Heath John R. (Sciendo, 1985)
Accepting that the activator appliance can be used successfully to correct the occlusion by modifying the relationship of the dentitions and modifying growth characteristics of maxilla and mandible, what are the limitations of the appliance in the treatment of Class II division I cases? How can we overcome these limitations to avoid the undesirable sequelae? Clinical experience with the Classical European Activator leads to the conclusion that this appliance does not provide adequate control of the position of the maxilla, and of the maxillary dentition. Unfavourable mandibular rotation may be induced. Excessive display of upper incisors may be increased. Similarly anterior high pull headgear attached to fixed appliances may also produce undesirable rotation of maxillary structures, particularly in patients showing dolichofacial characteristics. A combination of these two treatment modalities has been developed by Dr. U. Teuscher of Zurich. This article in essence represents an analysis of clinical results in which the activator with anterior high pull headgear was used in patients chosen from the author's practice. The aim is to help the clinician appreciate the far reaching potential of the Teuscher appliance. Because the objective of this article is motivational, references are provided that should enable the clinician to manufacture and use the appliance, and to integrate the concept into their overall management of our Class II division 1 cases.